Catcalling sebagai Bentuk Pelecehan Seksual Traumatis - Qila, Saffana Zahro; Rahmadina, Rizki Nur; Azizah, Fadhlin (Jurnal Mahasiswa Komunikasi Cantrik, 2021)
Catcalling events are now quite familiar, especially in big cities like Yogyakarta, where the population is full of students and college students. Catcalling involves a different experience for everyone. The purpose of this study was to know in depth the experiences and reactions of a person when experiencing catcalling. This research is qualitative research using the phenomenological method. The results of this study indicate that catcalling is a form of verbal sexual harassment and has a negative impact on the victim’s life. The informant who became a victim of catcalling chose to remain silent even though it had a deep impact, even to a traumatic experience. Therefore, victims need to voice their interests to get wide attention. Keywords: catcalling, experience, reaction, sexual harassment, verbal communication,